Automatic Wastafel Touchless With Solar Cell as Alternative Energy Sources - Zainal Arifin; Indah Sulistiyowati (Universitas Muhammadiyah Sidoarjo, 2021)
One way to prevented and breaked the chain of spreaded the Covid-19 virus is to handle it. By diligently used soap for at least 20 seconds, it can prevened transmission of the Covid 19 virus. Because hands are the part that is often exposed to direct interaction. So that bacteria and viruses can easily stick to the hands. Therefore an innovation is needed to make a touchless automatic sink that will touch the touch of the hand both when taked soap, washed hands with air and then dryed hands with a hand dryer so that they touch the touch with objects. This automatic sink was innovated using Solar Cell as an alternative energy to electric power. The solar cell used is 30 WP. This tool uses an IR Infrared Obstacle Avoidance sensor as input. Water pump, soap pump, hand dryer will each operate a sensor which has a hitch. The test results show the sensor can detected an obstacle 2-10cm away. The energy produced by the solar cell based on the test results obtained at 50-100% power, the tool can function properly, but at battery power below 50% indicates a decrease in function, namely the hand dryer cannot function.